Avaliação do Potencial de Actividades em Sistemas de Uso Múltiplo: Aptidão Forrageira - Alpendre, Pedro; Gonçalves, Ana Cristina; Ferreira, Alfredo Gonçalves; Dias, Susana Saraiva (Silva Lusitana, 2008)
Multiple use systems are characterised by the presence of several cultures in a management unit. These cultures present their own characteristics and several productions, with different spatial and temporal arrangements. In Alentejo the most representative systems, in terms of area, are the "montados", agro-silvo-pastoral systems, characterised by three main components, forest, agriculture and grazing, and the interrelations among them. In these systems the grazing component and, consequently, the pasture is a fundamental activity for the system maintenance/perpetuity. The goal of this study is to create a methodology that defines the forage aptitude of the "montado", as function of the soil and forest cover. The utilisation of spatial analysis processes, in geographical information systems, allowed the development of an innovative methodology, constituting an evaluation and implementation information tool.
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: activités en systèmes d; aptitude de; evaluation du potentiel des; evaluation tool; forage aptitude; forest cover; GIS; les systèmes d; par la présence de; plusieurs cultures; production fourragère; résumé; soils; usage multiple; usage multiple sont caractérisés

Avaliação do Potencial de Actividades em Sistemas de Uso Múltiplo: Aptidão Forrageira (Silva Lusitana, 2008)
Multiple use systems are characterised by the presence of several cultures in a management unit. These cultures present their own characteristics and several productions, with different spatial and temporal arrangements. In Alentejo the most representative systems, in terms of area, are the "montados", agro-silvo-pastoral systems, characterised by three main components, forest, agriculture and grazing, and the interrelations among them. In these systems the grazing component and, consequently, the pasture is a fundamental activity for the system maintenance/perpetuity. The goal of this study is to create a methodology that defines the forage aptitude of the "montado", as function of the soil and forest cover. The utilisation of spatial analysis processes, in geographical information systems, allowed the development of an innovative methodology, constituting an evaluation and implementation information tool.